A new algorithm for optimizing the wavelength coverage for spectroscopic studies: Spectral Wavelength Optimization Code (swoc). Issue 2 (8th June 2016) - Ruchti, G. R.; Feltzing, S.; Lind, K.; Caffau, E.; Korn, A. J.; Schnurr, O.; Hansen, C. J.; Koch, A.; Sbordone, L.; de Jong, R. S.
Abstract: The past decade and a half has seen the design and execution of several ground-based spectroscopic surveys, both Galactic and Extragalactic. Additionally, new surveys are being designed that extend the boundaries of current surveys. In this context, many important considerations must be done when designing a spectrograph for the future. Among these is the determination of the optimum wavelength coverage. In this work, we present a new code for determining the wavelength ranges that provide the optimal amount of information to achieve the required science goals for a given survey. In its first mode, it utilizes a user-defined list of spectral features to compute a figure-of-merit for different spectral configurations. The second mode utilizes a set of flux-calibrated spectra, determining the spectral regions that show the largest differences among the spectra. Our algorithm is easily adaptable for any set of science requirements and any spectrograph design. We apply the algorithm to several examples, including 4MOST, showing the method yields important design constraints to the wavelength regions.